The Accuracy of The Malnutrition Screening Tool (MST) for Identifying Malnutrition Risk in Stroke Patient (Journal of Tropical Pharmacy and Chemistry, 2025)
Malnutrition in stroke patients is associated with poor clinical outcomes, making early nutritional assessment essential, as it is a modifiable risk factor. The Malnutrition Screening Tool (MST) offers a rapid and simple approach for nutritional screening; however, its application in stroke populations remains limited. This study aimed to evaluate the diagnostic accuracy of the MST compared with the Subjective Global Assessment (SGA) in stroke patients. A cross-sectional study was conducted involving 96 acute stroke patients at Atma Jaya Hospital, Jakarta, using retrospective medical records. The MST was employed for nutritional screening, while nutritional status was determined using the SGA. Bivariate analyses assessed associations between patient characteristics, MST scores, Body Mass Index (BMI), hemoglobin levels, and total lymphocyte count (TLC) with SGA classification. Logistic regression was used to determine the independent association between MST scores and nutritional status, and the Area Under the Curve (AUC) was calculated to evaluate MST validity. Results showed that 25% of patients were malnourished according to the SGA. Age, BMI, hemoglobin, TLC, and MST scores were significantly associated with nutritional status (p < 0.05). An MST score ≥2 increased the odds of malnutrition by 3.115 (p < 0.05). The MST demonstrated 75.0% sensitivity, 51.4% specificity, and an AUC of 0.674, indicating adequate diagnostic performance, though complementary assessment tools are recommended.